Worldwide distribution patterns of the planktonic shelled protists Radiolaria (Polycystina) and Foraminifera: Similarities and contrasts - Boltovskoy, Demetrio; Correa, Nancy (Paleontological Journal)
Abstract: Planktonic Foraminifera and Polycystina (Radiolaria) depict roughly similar—but not identical—worldwide distribution patterns. Discrepancies affect both cold- and warmwater areas, as well as the latitudinal profile of species richness, which peaks at the equator in Radiolaria, but in the subtropics in Foraminifera. Some differences are probably due to group-specific dissimilarities, but preservational and methodological artifacts play a key role. Fil: Boltovskoy, Demetrio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Ecología, Genética y Evolución de Buenos Aires; Argentina Fil: Correa, Nancy. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval; Argentina